[Banyan, Port of Spain, 1937] - (:unkn) unknown (My University, 2010)
A Banyan tree located in a public square in Trinidad, 1937.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Parks--Trinidad and Tobago; 1937; Banyan trees--Trinidad and Tobago